Molecular Classification of Ependymal Tumors across All CNS Compartments, Histopathological Grades, and Age Groups - Pajtler, Kristian W; Witt, Hendrik; Sill, Martin; Jones, David T W; Hovestadt, Volker; Kratochwil, Fabian; Wani, Khalida; Tatevossian, Ruth; Punchihewa, Chandanamali; Johann, Pascal; Reimand, Jüri; Warnatz, Hans-Jörg; et al. (Cancer cell, 2015)
Ependymal tumors across age groups are currently classified and graded solely by histopathology. It is, however, commonly accepted that this classification scheme has limited clinical utility based on its lack of reproducibility in predicting patients' outcome. We aimed at establishing a uniform molecular classification using DNA methylation profiling. Nine molecular subgroups were identified in a large cohort of 500 tumors, 3 in each anatomical compartment of the CNS, spine, posterior fossa, supratentorial. Two supratentorial subgroups are characterized by prototypic fusion genes involving RELA and YAP1, respectively. Regarding clinical associations, the molecular classification proposed herein outperforms the current histopathological classification and thus might serve as a basis for the next World Health Organization classification of CNS tumors.
Keywords: genetická transkripce; Gene Fusion; Infant; Humans; fosfoproteiny; kojenec; lidé středního věku; dítě; Transcription Factors; Child; Transcription, Genetic; Female; Aged; mladý dospělý; adaptorové proteiny signální transdukční; dospělí; genová dávka; věkové faktory; senioři; lidé; Adaptor Proteins, Signal Transducing; nádory centrálního nervového systému; předškolní dítě; Adult; Ependymoma; YAP-Signaling Proteins; DNA Methylation; Central Nervous System Neoplasms; metylace DNA; ženské pohlaví; Male; Middle Aged; Adolescent; stanovení celkové genové exprese; Young Adult; ependymom; signální proteiny YAP; transkripční faktory; fúze genů; Age Factors; Gene Expression Profiling; mužské pohlaví; Child, Preschool; Phosphoproteins; Gene Dosage; mladiství